Gino Luzzatto and the contested place of Jews in the economic history of Mediterranean Europe. Issue 2 (3rd July 2022) - Munari, Tommaso; Trivellato, Francesca
Abstract : The few Anglophone readers for whom the name Gino Luzzatto (1878–1964) still has a familiar ring know him as an economic historian of medieval Europe, with a focus on Italy and on Mediterranean trade. But throughout his career he also cultivated a consistent if secondary interest in Jewish history and weighed in on controversial debates on the role of Jews in the development of Western capitalism. A socialist and an assimilated Jew, Luzzatto was persecuted first for his political ideas and later as a consequence of Mussolini's Racial Laws. This article examines his largely forgotten contributions to the economic history of medieval and early modern Italian Jews in order to illuminate a little-known chapter in the ever-contentious relationship between economic history and Jewish history. By placing Luzzatto alongside his contemporaries, it elucidates his commitment to integrate Jewish history into general European history and compares his approach to competing interpretations dating from the inter-war and immediate post-war periods. It thus broadens our knowledge of the range of scholarly traditions that have sustained the study of Jews' economic roles before the current revival of interest in the topic.